Tetten ért intermedialitás Michael Haneke A zongoratanárnő c. filmjében - Nádudvari Gabriella; Haneke Michael; Tudományos és művészeti műhelymunkák : új utakon a pedagógusképző kar (2007) (Szeged) (2009)
The paper provides an overview of the latest results of German-language research into film narratology. In addition, based on Yvonne Spielmann’s intermediality theory, the author examines how the hypertext of Michael Haneke's film Die Klavierspielerin is related to the hypertext of the Elfriede Jelinek’s novel, Die Klavierspielerin. Analysis of text-production methods reveal that figures of vertical intermediality become more dense, while repetitions lengthen both the literary and the film text. These two methods, although with different intensity and dominance, clash and transform into ideas in both texts.